Preparation method and application of Cu-BTC / phoenix tree flocculus biomass charcoal composite material

Through the preparation of Cu-BTC/Wutonghuo biomass carbon composite, the problem of mass transfer resistance caused by high synthesis cost and small pore size of MOFs nanomaterials is solved, and the NO2 gas transmission with high selectivity and high sensitivity at room temperature is achieved Excellent sense, material stability and response speed, suitable for low-cost applications.

CN119125232AActive Publication Date: 2024-12-13QINGDAO BINHAI UNIV

Patent Information

Application Number
CN202411248726.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2024-12-13
Estimated Expiration
2044-09-06

AI Technical Summary

Technical Problem

The existing MOFs nanomaterials have high synthesis cost and complex synthesis process, are easy to accumulate and have small pore size, resulting in large mass transfer resistance of gas, limiting sensing efficiency.

Method used

The preparation method of Cu-BTC/Wutonghuo biomass carbon composite material is adopted to prepare materials with porous structures through the host-guest coupling construction strategy, combining biomass carbon and Cu-BTC to form a tight interface and improve gas sensing performance.

Benefits of technology

It realizes high selectivity and high sensitivity NO2 gas sensing at room temperature, with good material stability, fast response speed and low cost, suitable for room temperature NO2 gas detection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119125232A_ABST
    Figure CN119125232A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a Cu-BTC / phoenix tree flocculus biomass charcoal composite material, and belongs to the technical field of room temperature gas sensing materials. The invention aims to solve the problems that the existing MOFs nano material is relatively high in synthesis cost, complex in synthesis process, easy to accumulate and relatively small in pore diameter, so that the gas mass transfer resistance is relatively large, and the sensing efficiency is limited. The phoenix tree flocculus porous carbon is prepared from phoenix tree flocculus by adopting a chemical activation and calcination combined process, and the biomass carbon material retains a natural tubular structure of biomass and is beneficial to adsorption or diffusion of to-be-detected gas. The Cu-BTC / phoenix tree flocculus biomass charcoal composite material is prepared from biomass charcoal derived from phoenix tree flocculus for the first time, and the Cu-BTC / phoenix tree flocculus biomass charcoal composite material is successfully applied to NO2 gas-sensitive application to solve the problems of low sensitivity, high detection limit, poor restorability, high cost and the like when NO2 is detected in the prior art. The method has the characteristics of simplicity and convenience in operation and high NO2 sensing efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of room temperature gas sensing materials, and particularly relates to a preparation method and application of a Cu-BTC / Pu Tong fluff biomass carbon composite material. Background Art

[0002] Nitrogen dioxide (NO2) is a toxic and harmful atmospheric pollutant that not only corrodes industrial production equipment and shortens its service life, but can also cause serious respiratory diseases. NO2 often coexists with other gases in the environment, and these gas molecules can easily interact with the surface of gas sensing materials, affecting the selectivity of the sensor. Effective environmental monitoring and health protection first require efficient and convenient detection methods and equipment. Therefore, the development of highly selective and sensitive NO2 gas sensors at room temperature is of great practical significance.

[0003] As a type of smart sensor, gas sensors play an important role in the field of smart sensing. Chemiresistance gas sensors have promoted the innovative development of the field of gas sensing with low power consumption, low cost and high sensitivity for harmful gas detection. Existing gas sensors mainly detect gases through two forms: chemical adsorption and physical adsorption. Chemical adsorption enhances the sensing response and selectivity by forming covalent bonds, but this binding method may lead to irreversible chemical changes. Although physical adsorption is suitable for real-time monitoring, it has problems of insufficient stability and lack of selectivity. Therefore, it is of great application value to explore gas sensing materials that are compatible with high selectivity and high sensitivity.

[0004] Metal-organic framework materials (MOFs) have shown great application potential in the field of gas sensing due to their unique structural characteristics and functionality. The structural diversity and large specific surface area of ​​MOFs nanomaterials provide a large number of adsorption sites for gas molecules, which helps to improve the sensitivity and selectivity of the sensor. By regulating the pore size and geometry of MOFs nanomaterials, selective adsorption of specific gas molecules can be achieved, thereby enhancing the specificity of the sensor. Although MOFs nanomaterials have great potential in gas sensing, the chemical stability, thermal stability and mechanical stability of MOFs nanomaterials are relatively poor, resulting in challenges in their practical applications. In addition, the synthesis cost of MOFs nanomaterials is high, the synthesis process is complex, and they are easy to stack and the small pore size may lead to large gas mass transfer resistance, limiting the sensing efficiency. In view of this, the practical application of MOFs nanomaterials in the field of gas sensors is greatly hindered. Summary of the invention

[0005] The purpose of the present invention is to solve the problems of high synthesis cost, complex synthesis process, easy accumulation and small pore size of existing MOFs nanomaterials, which may lead to large gas mass transfer resistance and limit the sensing efficiency, and to provide a preparation method and application of Cu-BTC / Putong fluff biomass charcoal composite material.

[0006] The present invention provides a preparation method and application of a Cu-BTC / Tung Blossom Fiber Biomass Carbon Composite Material with a special hierarchical porous structure based on a host-guest coupling construction strategy. The present invention has low preparation condition requirements, simple operation, low energy consumption, and is environmentally friendly. The obtained gas sensing material has a tight interface bonding between the two components, has excellent room temperature NO2 gas sensing performance and stability, and the phase and morphology structure of the composite material are easy to control, providing important technical support for the development and application of efficient room temperature NO2 gas sensing materials.

[0007] A method for preparing a Cu-BTC / Pu Tong fluff biomass carbon composite material is specifically completed by the following steps:

[0008] 1. Preparation of porous thin-layer tubular structure of tung oil cotton wool porous carbon:

[0009] ①, washing the collected tung oil cotton wool, and then drying it to obtain pre-treated tung oil cotton wool;

[0010] ②, soak the pretreated tung oil floss in NaOH solution, stir at room temperature for a period of time, then let it stand for a period of time, then dry it, and finally heat it to the calcination temperature in a carbonization atmosphere, calcine it at the calcination temperature for a period of time to obtain a reaction product;

[0011] ③, washing the reaction product and drying it to obtain porous thin-layer tubular structure of tung oil linden fiber porous carbon;

[0012] 2. Preparation of Cu-BTC / Putong cotton biomass carbon composite material:

[0013] ① Dissolve copper salt in deionized water to obtain solution Ⅰ;

[0014] ②, adding the organic ligand and polyvinyl pyrrolidone to the mixture of N,N-dimethylformamide and anhydrous ethanol, firstly ultrasonically treating, then magnetically stirring, to obtain solution II;

[0015] ③. Mix solution I and solution II to obtain a mixed solution; immerse the porous thin-layer tubular structure of the tung oil tree fiber porous carbon into the mixed solution, let it stand for a period of time, and then transfer it to a polytetrafluoroethylene-lined stainless steel high-pressure reactor, and then heat it at 80℃~120℃ for 10h~12h, cool to room temperature, wash, and centrifuge again, collect the precipitate after centrifugation, and finally dry it to obtain the Cu-BTC / tung oil tree fiber biomass carbon composite material.

[0016] A Cu-BTC / Phoenix tung oil biomass carbon composite material is used to prepare gas sensors.

[0017] Principle of the present invention:

[0018] The present invention provides a simple solvent-thermal method to prepare a composite material of biochar anchored Cu-BTC and the application of the composite material to NO2 gas sensing at room temperature; the present invention prepares the Cu-BTC material by a simple method to solve the problem of size controllability of MOF-based materials; the present invention provides a simple heat treatment method to prepare a porous tubular biochar using Chinese parasol floss as a raw material to solve the problem that a large number of micropores in the biochar hinder the diffusion of gas molecules; the present invention supports and disperses the Cu-BTC material by anchoring the composite material of the host Cu-BTC with the guest biochar, thereby obtaining a gas sensing material with a large specific surface area and abundant active sites, thereby increasing the contact between the gas to be measured and the sensing material, shortening the transmission path of the carrier, and improving the sensitivity and selectivity of the gas sensing.

[0019] The present invention has the following beneficial effects:

[0020] (1) The Cu-BTC / Phoenix tung oil biomass carbon composite material provided by the present invention has a porous hierarchical nanotube structure in the form of biomass. The porous hierarchical nanostructure can effectively reduce the working temperature and obtain higher NO2 gas sensitivity and response speed;

[0021] (2) The Cu-BTC / Tung Blossom Fiber Biomass Carbon Composite Material provided by the present invention is an organic metal skeleton nanomaterial, forming a metal skeleton material structure of a regular hexahedron. The high and fine XRD diffraction peaks indicate that the material has good crystallinity, thereby increasing its ability to resist interference from the external environment and making its performance stable;

[0022] (3) The Cu-BTC / Pu Tong fluff biomass charcoal composite material and pure Cu-BTC provided by the present invention are used as gas sensing materials to detect NO2 gas in the air. No heating system is required and detection can be performed at room temperature. The working temperature is low and the operating conditions are mild.

[0023] (4) The Cu-BTC / Tung Blossom Fiber Biomass Carbon Composite Material provided by the present invention is used as a gas sensing material for detecting NO2 gas in the air. It can be operated at room temperature, i.e., 20°C to 35°C, and humidity of 20% to 50%. Under these conditions, the sensitivity of the composite material to NO2 gas with a concentration of 50ppm is as high as 39.54, and the sensitivity to NO2 gas with a concentration as low as 0.03ppm is 1.27, and the gas sensing performance is excellent; the time taken for the sensitive membrane to change from the beginning of the resistance change when NO2 gas is injected from 50ppm to 1ppm to the time when its resistance is completely stable is less than 20s, the response speed is fast, and the adsorption reversibility is good without external influence, and the method of use is simple;

[0024] (5) The preparation method of the Cu-BTC / Tung Blossom Fiber Biomass Carbon Composite Material provided by the present invention is simple to operate, low in cost, and easy to promote. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a scanning electron microscopy image of Cu-BTC prepared in Comparative Example 1;

[0026] Figure 2 The electron scanning electron micrographs of the biomass charcoal prepared in Comparative Example 2 and the porous thin-layer tubular structure of the tung oil linden porous charcoal prepared in Step 1 of Example 1, wherein (a) and (b) are the biomass charcoal prepared in Comparative Example 2, and (c) and (d) are the porous thin-layer tubular structure of the tung oil linden porous charcoal prepared in Step 1 of Example 1;

[0027] Figure 3 This is a scanning electron micrograph of the Cu-BTC / Phoenix tung blossom biomass carbon composite material prepared in Example 1;

[0028] Figure 4 for Figure 3 A local magnified electron scanning electron microscope image;

[0029] Figure 5 X-ray diffraction patterns of Cu-BTC prepared in Comparative Example 1 and Cu-BTC / Putong fluff biomass carbon composite material prepared in Example 1;

[0030] Figure 6 This is the thermogravimetric curve of sycamore fluff in air atmosphere;

[0031] Figure 7 The sensitivity curves of the gas sensor prepared by using Cu-BTC prepared in Comparative Example 1 as the sensitive material to detect different concentrations of NO2 are shown in FIG.

[0032] Figure 8This is a sensitivity curve diagram of the gas sensor prepared by using the Cu-BTC / Tung Blossom Fiber biomass carbon composite material prepared in Example 1 as the sensitive material to detect different concentrations of NO2. Specific implementation methods

[0034] Specific implementation method 1: This implementation method is a method for preparing a Cu-BTC / Phoenix tung oil biomass carbon composite material, which is specifically completed by the following steps:

[0035] 1. Preparation of porous thin-layer tubular structure of tung oil cotton wool porous carbon:

[0036] ①, washing the collected tung oil cotton wool, and then drying it to obtain pre-treated tung oil cotton wool;

[0037] ②, soak the pretreated tung oil floss in NaOH solution, stir at room temperature for a period of time, then let it stand for a period of time, then dry it, and finally heat it to the calcination temperature in a carbonization atmosphere, calcine it at the calcination temperature for a period of time to obtain a reaction product;

[0038] ③, washing the reaction product and drying it to obtain porous thin-layer tubular structure of tung oil linden fiber porous carbon;

[0039] 2. Preparation of Cu-BTC / Putong cotton biomass carbon composite material:

[0040] ① Dissolve copper salt in deionized water to obtain solution Ⅰ;

[0041] ②, adding the organic ligand and polyvinyl pyrrolidone to the mixture of N,N-dimethylformamide and anhydrous ethanol, firstly ultrasonically treating, then magnetically stirring, to obtain solution II;

[0042] ③. Mix solution I and solution II to obtain a mixed solution; immerse the porous thin-layer tubular structure of the tung oil tree fiber porous carbon into the mixed solution, let it stand for a period of time, and then transfer it to a polytetrafluoroethylene-lined stainless steel high-pressure reactor, and then heat it at 80℃~120℃ for 10h~12h, cool to room temperature, wash, and centrifuge again, collect the precipitate after centrifugation, and finally dry it to obtain the Cu-BTC / tung oil tree fiber biomass carbon composite material.

[0043] Specific implementation method 2: The difference between this implementation method and specific implementation method 1 is that: in step 1①, the collected sycamore cotton wool is washed 2 to 4 times with anhydrous ethanol, and then dried at 60℃ to 80℃ for 10h to 12h; the concentration of the NaOH solution described in step 1② is 0.5mol / L to 3mol / L; in step 1②, the pretreated sycamore cotton wool is immersed in the NaOH solution, stirred at room temperature for 1h to 2h, then allowed to stand and soak for 8h to 10h, and then dried at 60℃ to 80℃ for 10h to 12h. The other steps are the same as those in specific implementation method 1.

[0044] Specific implementation method three: This implementation method is different from specific implementation methods one or two in that: the carbonization atmosphere described in step one ② is air, nitrogen or argon; in step one ②, the temperature is raised from room temperature to 300℃~450℃ at a heating rate of 5℃ / min~10℃ / min under the carbonization atmosphere, and calcined at 300℃~450℃ for 30min~240min; in step one ③, the reaction product is washed with deionized water to neutrality, and then dried at 60℃~80℃ for 10h~12h to obtain a porous thin-layer tubular structure of sycamore cotton wool porous carbon. The other steps are the same as those of specific implementation methods one or two.

[0045] Specific embodiment 4: This embodiment differs from specific embodiments 1 to 3 in that: the copper salt described in step 2① is copper nitrate or copper sulfate; the mass ratio of the copper salt described in step 2① to the volume ratio of deionized water is (2.5g to 4.5g):30mL. The other steps are the same as those of specific embodiments 1 to 3.

[0046] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that: the organic ligand described in step 2 ② is 1,4-phthalic acid, 1,3,5-benzenetricarboxylic acid or 1,2-dimethylimidazole; the molecular weight of polyvinylpyrrolidone described in step 2 ② is 58000, 24000 or 1300000; the volume ratio of N,N-dimethylformamide and anhydrous ethanol in the mixed solution of N,N-dimethylformamide and anhydrous ethanol described in step 2 ② is (20-50): (20-50). The other steps are the same as specific embodiments 1 to 4.

[0047] Specific embodiment 6: This embodiment differs from specific embodiments 1 to 5 in that: the mass volume ratio of the organic ligand, polyvinyl pyrrolidone, N,N-dimethylformamide and anhydrous ethanol described in step 2 ② is (1g-2g): (1g-2g): 60mL; the ultrasonic treatment time described in step 2 ② is 5min-10min, the magnetic stirring time is 15min-60min, and the magnetic stirring speed is 500r / min-800r / min. The other steps are the same as those of specific embodiments 1 to 5.

[0048] Specific embodiment 7: This embodiment differs from specific embodiments 1 to 6 in that: the volume ratio of solution I and solution II in step 2 ③ is 1:2; the standing time in step 2 ③ is 10h to 12h; the washing in step 2 ③ is washing with deionized water and anhydrous ethanol 2 to 4 times in sequence; the drying temperature in step 2 ③ is 60℃ to 80℃, and the drying time is 5h to 10h. The other steps are the same as those in specific embodiments 1 to 6.

[0049] Specific implementation method eight: This implementation method is a Cu-BTC / Phoenix tree fluff biomass carbon composite material used for preparing gas sensors.

[0050] Specific embodiment 9: The difference between this embodiment and specific embodiments 1 to 8 is that a Cu-BTC / Phoenix tung wood fiber biomass carbon composite material is used to prepare a gas sensor, which is completed in the following steps: adding the Cu-BTC / Phoenix tung wood fiber biomass carbon composite material to anhydrous ethanol, ultrasonically dispersing it to obtain a uniformly dispersed suspension; spin-coating the uniformly dispersed suspension on an Au interdigital electrode, drying it at room temperature, and obtaining a gas sensor; the mass ratio of the Cu-BTC / Phoenix tung wood fiber biomass carbon composite material to the volume of anhydrous ethanol is (0.01g~0.05g):(0.3mL~1.0mL); the volume ratio of the uniformly dispersed suspension to the surface area of ​​the Au interdigital electrode is (0.03mL~0.15mL):0.25cm 2 The other steps are the same as those in Specific Embodiments 1 to 8.

[0051] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that the gas sensor is used to detect low-concentration NO2 gas in the air at room temperature, with a detection limit as low as 30 ppb. The other steps are the same as those of specific embodiments 1 to 9.

[0052] The following examples are used to verify the beneficial effects of the present invention:

[0053] Comparative Example 1: The preparation method of Cu-BTC is specifically completed according to the following steps:

[0054] 4.25 g of copper nitrate was dissolved in 30 mL of deionized water and stirred to form a transparent solution; then, 2.0 g of 1,3,5-benzenetricarboxylic acid (H3BTC) and 2.0 g of PVP (molecular weight of 1300000) were mixed in a mixed solution of 30 mL of N,N-dimethylformamide (DMF) and 30 mL of anhydrous ethanol, and then ultrasonic treatment was performed for 5 min and magnetic stirring was performed for 30 min to mix the two solutions to form a precursor mixed solution; the precursor mixed solution was transferred to a polytetrafluoroethylene-lined stainless steel autoclave (100 mL) and heated at 100 ° C for 10 hours. After cooling to room temperature, the blue Cu-BTC crystals were centrifuged and dried at 60 ° C for 7 hours to obtain Cu-BTC.

[0055] Comparative Example 2: Biochar prepared by non-activation method is specifically completed by the following steps:

[0056] ①, using anhydrous ethanol to wash the collected sycamore cotton wool three times, and then drying it at 80°C for 12 hours to obtain pretreated sycamore cotton wool;

[0057] ②, heating the pretreated tung oil cotton to 400°C at a heating rate of 5°C / min in an air atmosphere, and calcining at 400°C for 120min to obtain a reaction product;

[0058] ③. The reaction product was washed with deionized water until it became neutral, and then dried at 80°C to obtain biochar.

[0059] Example 1: A method for preparing a Cu-BTC / Phoenix tung oil biomass carbon composite material, which is specifically completed by the following steps:

[0060] 1. Preparation of porous thin-layer tubular structure of tung oil cotton wool porous carbon:

[0061] ①, using anhydrous ethanol to wash the collected sycamore cotton wool three times, and then drying it at 80°C for 12 hours to obtain pretreated sycamore cotton wool;

[0062] ②, soak the pretreated sycamore cotton wool in a 1 mol / L NaOH solution, stir at room temperature for 1 h, then stand and soak for 10 h, then dry at 80 ° C for 12 h, and finally heat from room temperature to 400 ° C at a heating rate of 5 ° C / min in an air atmosphere, and calcine at 400 ° C for 120 min to obtain a reaction product;

[0063] ③, washing the reaction product with deionized water until it is neutral, and then drying it at 80°C to obtain a porous thin-layer tubular structure of tung oil porous carbon;

[0064] 2. Preparation of Cu-BTC / Putong cotton biomass carbon composite material:

[0065] ① Dissolve 4.25 g of copper nitrate in 30 mL of deionized water to obtain solution I;

[0066] ②, 2.0 g 1,3,5-benzenetricarboxylic acid (H3BTC) and 2.0 g PVP (molecular weight 1300000) were mixed in a mixture of 30 mL N,N-dimethylformamide (DMF) and 30 mL anhydrous ethanol, first ultrasonically treated for 5 min, then magnetically stirred for 30 min at a speed of 500 r / min to obtain solution II;

[0067] ③. Mix solution I and solution II to obtain a mixed solution; immerse the porous thin-layer tubular structure of the tung oil tree fiber porous carbon into the mixed solution, let it stand for 12 hours, and then transfer it to a polytetrafluoroethylene-lined stainless steel high-pressure reactor (100 mL), and then heat it at 100°C for 10 hours, cool to room temperature, wash it with deionized water and anhydrous ethanol for 3 times in sequence, and then centrifuge it, collect the precipitate after centrifugation, and finally dry it at 60°C for 8 hours to obtain the Cu-BTC / tung oil tree fiber biomass carbon composite material.

[0068] Figure 1 This is a scanning electron microscopy image of Cu-BTC prepared in Comparative Example 1;

[0069] Depend on Figure 1 It can be seen that Cu-BTC has a regular hexahedral structure and a particle size of 1-2 microns.

[0070] Figure 2 The electron scanning electron micrographs of the biomass charcoal prepared in Comparative Example 2 and the porous thin-layer tubular structure of the tung oil linden porous charcoal prepared in Step 1 of Example 1, wherein (a) and (b) are the biomass charcoal prepared in Comparative Example 2, and (c) and (d) are the porous thin-layer tubular structure of the tung oil linden porous charcoal prepared in Step 1 of Example 1;

[0071] Depend on Figure 2 (a) and (b) show that the unactivated biochar presents a smooth tubular structure with an inner diameter of about 40-60 μm; while the activated biochar tube wall becomes significantly thinner and presents a distinct sparse pore structure ( Figure 2 (c) and (d)).

[0072] Figure 3 This is a scanning electron micrograph of the Cu-BTC / Phoenix tung blossom biomass carbon composite material prepared in Example 1;

[0073] from Figure 3 It can be seen that Cu-BTC nanoparticles are evenly wrapped on the surface of biochar.

[0074] Figure 4 for Figure 3 A local magnified electron scanning electron microscope image;

[0075] from Figure 4 It can be seen that the composite Cu-BTC still retains a complete hexahedral structure, but some round particles are produced on its surface.

[0076] Figure 5 X-ray diffraction patterns of Cu-BTC prepared in Comparative Example 1 and Cu-BTC / Putong fluff biomass carbon composite material prepared in Example 1;

[0077] Figure 5 This can prove the successful preparation of Cu-BTC material; the X-ray diffraction peak of Cu-BTC / biomass carbon composite material is lower in intensity than that of Cu-BTC, and the (111) and (200) diffraction peaks of Cu element appear.

[0078] Figure 6 This is the thermogravimetric curve of sycamore fluff in air atmosphere;

[0079] Figure 6It can be observed that the sycamore cotton material undergoes an obvious weight loss carbonization process at 300°C to 450°C when calcined in air. Therefore, the carbonization temperatures selected in Examples 1 and 5 are 300°C, 350°C, 400°C, and 450°C.

[0080] Comparative Application Example 1: The gas sensor prepared by using the Cu-BTC prepared in Comparative Example 1 as the sensitive material is completed according to the following steps:

[0081] 0.05 g of Cu-BTC prepared in Comparative Example 1 was ultrasonically dispersed in 0.5 mL of anhydrous ethanol to obtain a uniformly dispersed suspension, which was then spin-coated on an Au interdigital electrode and dried at room temperature to obtain a gas sensor; the ratio of the volume of the uniformly dispersed suspension to the surface area of ​​the Au interdigital electrode was 0.05 mL:0.25 cm 2 .

[0082] The gas sensor prepared in Example 1 was used to detect its sensitivity to NO2 in the air environment. The results are shown in Tables 1 and Figure 7 shown.

[0083] Table 1 Comparison of the results of NO2 detection by the gas sensor prepared in Example 1

[0084]

[0085]

[0086] Figure 7 The sensitivity curves of the gas sensor prepared by using Cu-BTC prepared in Comparative Example 1 as the sensitive material to detect different concentrations of NO2 are shown in FIG.

[0087] From Table 1 and Figure 7 It can be seen that the sensitivity of the gas sensor prepared in Example 1 to NO2 gas with a concentration of 1 ppm is as high as 3.63, that is, the gas sensor has certain response and recovery characteristics to NO2; the time taken for the sensitive membrane to change from the beginning of resistance change when 1 ppm NO2 gas is injected to the time when its resistance is completely stable is less than 20s, the response speed is fast, the adsorption reversibility is good, and the method of use is simple.

[0088] Among them, sensitivity S = R a / R g , R a is the initial resistance of the gas sensor in air environment, R g is the resistance of the gas sensor in NO2 atmosphere.

[0089] Application Example 1: The gas sensor prepared by using the Cu-BTC / Tung Blossom Biomass Carbon Composite Material prepared in Example 1 as a sensitive material is completed by the following steps:

[0090] 0.05 g of the Cu-BTC / Tung Blossom Biomass Carbon Composite Material prepared in Example 1 was ultrasonically dispersed in 0.5 mL of anhydrous ethanol to obtain a uniformly dispersed suspension, which was then spin-coated on an Au interdigital electrode and dried at room temperature to obtain a gas sensor; the ratio of the volume of the uniformly dispersed suspension to the surface area of ​​the Au interdigital electrode was 0.05 mL:0.25 cm 2 .

[0091] The gas sensor prepared in Example 1 was used to detect its sensitivity to NO2 in the air environment. The results are shown in Tables 2 and Figure 8 shown.

[0092] Table 2 Results of using the gas sensor prepared in Example 1 to detect NO2

[0093]

[0094]

[0095] Figure 8 The sensitivity curve diagram of the gas sensor prepared by using the Cu-BTC / Pu Tong cotton wool biomass carbon composite material prepared in Example 1 as the sensitive material to detect different concentrations of NO2;

[0096] From Table 2 and Figure 8 It can be seen that the sensitivity of the gas sensor prepared in Example 1 to NO2 gas with a concentration of 50ppm is as high as 39.54, that is, the gas sensor has good response and recovery characteristics to NO2; the time taken for the sensitive membrane to change from the beginning of the NO2 gas resistance change when the NO2 gas is injected from 50ppm to 1ppm to the complete stabilization of its resistance is less than 15s, with fast response speed, good adsorption reversibility and simple use.

[0097] Example 2: The difference between this example and Example 1 is that the difference between this embodiment and the specific embodiment 1 is that: in step 1①, the collected sycamore cotton wool is washed 3 times with anhydrous ethanol and then dried at 60℃ for 12h; the concentration of the NaOH solution described in step 1② is 0.5mol / L; in step 1②, the pretreated sycamore cotton wool is immersed in the NaOH solution, stirred at room temperature for 1h, then allowed to stand and soak for 8h, and then dried at 60℃ for 12h. The other steps are the same as the specific embodiment 1.

[0098] Application Example 2: The difference between this application example and application example 1 is that the Cu-BTC / Phoenix tung blossoms biomass carbon composite material prepared in example 1 is replaced by the Cu-BTC / Phoenix tung blossoms biomass carbon composite material prepared in example 2. The other steps and parameters are the same as those in application example 1.

[0099] Example 3: The difference between this example and Example 1 is that the difference between this embodiment and one of the specific embodiments 1 or 2 is that the carbonization atmosphere described in step 1 ② is nitrogen; in step 1 ②, the temperature is raised from room temperature to 450°C at a heating rate of 5°C / min under the carbonization atmosphere, and calcined at 450°C for 120min; in step 1 ③, the reaction product is washed with deionized water to neutrality, and then dried at 60°C for 12h to obtain a porous thin-layer tubular structure of tung tree wool porous carbon. The other steps are the same as those of specific embodiments 1 or 2.

[0100] Application Example 3: The difference between this application example and application example 1 is that the Cu-BTC / Phoenix tung blossoms biomass carbon composite material prepared in example 1 is replaced by the Cu-BTC / Phoenix tung blossoms biomass carbon composite material prepared in example 3. The other steps and parameters are the same as those in application example 1.

[0101] Example 4: The difference between this example and Example 1 is that the copper salt described in step 2① is copper sulfate; the mass ratio of copper sulfate described in step 2① to deionized water is 3.2g:30mL. Other steps and parameters are the same as those in Example 1.

[0102] Application Example 4: The difference between this application example and application example 1 is that the Cu-BTC / Phoenix tung blossoms biomass carbon composite material prepared in example 1 is replaced by the Cu-BTC / Phoenix tung blossoms biomass carbon composite material prepared in example 4. The other steps and parameters are the same as those in application example 1.

[0103] Example 5: The difference between this example and Example 1 is that in step 2②, 1,3,5-benzenetricarboxylic acid (H3BTC) is replaced by 1,2-dimethylimidazole; the molecular weight of polyvinylpyrrolidone (PVP) described in step 2② is 58000. Other steps and parameters are the same as those in Example 1.

[0104] Application Example 5: The difference between this application example and application example 1 is that the Cu-BTC / Phoenix tung blossoms biomass carbon composite material prepared in example 1 is replaced by the Cu-BTC / Phoenix tung blossoms biomass carbon composite material prepared in example 5. The other steps and parameters are the same as those in application example 1.

[0105] The sensitivity results of the gas sensors prepared in Application Example 1 and Application Examples 1 to 5 for detecting 50 ppm of NO2 are shown in Table 3.

[0106] Table 3

[0107] serial number Sensitivity Response time(s) Comparative Application Example 1 3.63 17.4 Application Example 1 39.54 9.4 Application Example 2 6.2 47.4 Application Example 3 4.5 28.9 Application Example 4 17.6 12.5 Application Example 5 15.9 28

[0108] In summary, when the Cu-BTC / sycamore fluff biomass charcoal composite material provided by the present invention is used as a gas sensitive material for detecting the NO2 concentration in the air, it does not require a heating system, can work at room temperature, and has a fast response speed, good recovery reversibility, a simple method of use, and a low production cost.

[0109] The Cu-BTC / Phoenix tung floss biomass carbon composite material prepared by the present invention can be operated at room temperature, i.e., 20°C to 35°C, and humidity of 20% to 40%, indicating that the environmental humidity has no significant effect on the gas-sensitive performance of the composite material. And under this condition, the sensitivity of the composite material to NO2 gas with a concentration of 50ppm is as high as 39.54, that is, the gas sensor has good response and recovery characteristics to NO2, and has high sensitivity; when the concentration of NO2 is 0.03ppm, the sensitivity is 1.27, and the actual detection limit of the gas sensor can reach 23ppb, and the time taken for the sensitive membrane to change from the beginning of the resistance change to the complete stability of its resistance when the NO2 gas is injected from 50ppm to 1ppm is less than 20s, the response speed is fast, the adsorption reversibility is good, and the method of use is simple. Therefore, compared with the single-component Cu-BTC material, the Cu-BTC / Phoenix tung floss biomass carbon composite material has greater advantages such as higher sensitivity, faster response time and lower detection limit, which lays a foundation for the efficient detection of low-concentration nitrogen dioxide at room temperature.

Claims

1. A method for preparing a Cu-BTC / Pu Tong cotton fiber biomass carbon composite material. Features The preparation method is specifically completed according to the following steps:

1. Preparation of porous thin-layer tubular structure of tung oil cotton wool porous carbon: ①, washing the collected tung oil cotton wool, and then drying it to obtain pre-treated tung oil cotton wool; ②, soak the pretreated tung oil floss in NaOH solution, stir at room temperature for a period of time, then let it stand for a period of time, then dry it, and finally heat it to the calcination temperature in a carbonization atmosphere, calcine it at the calcination temperature for a period of time to obtain a reaction product; ③, washing the reaction product and drying it to obtain porous thin-layer tubular structure of tung oil linden fiber porous carbon; 2. Preparation of Cu-BTC / Pu Tong Floc Biomass Carbon Composite Material: ① Dissolve copper salt in deionized water to obtain solution Ⅰ; ②, adding the organic ligand and polyvinyl pyrrolidone to the mixture of N,N-dimethylformamide and anhydrous ethanol, firstly ultrasonically treating, then magnetically stirring, to obtain solution II; ③. Mix solution I and solution II to obtain a mixed solution; immerse the porous thin-layer tubular structure of the tung oil tree fiber porous carbon into the mixed solution, let it stand for a period of time, and then transfer it to a polytetrafluoroethylene-lined stainless steel high-pressure reactor, and then heat it at 80℃~120℃ for 10h~12h, cool to room temperature, wash, and centrifuge again, collect the precipitate after centrifugation, and finally dry it to obtain the Cu-BTC / tung oil tree fiber biomass carbon composite material.

2. A method for preparing a Cu-BTC / Pu Tong fluff biomass carbon composite material according to claim 1, Features In step 1①, the collected sycamore fluff is washed 2 to 4 times with anhydrous ethanol, and then dried at 60°C to 80°C for 10 to 12 hours; the concentration of the NaOH solution described in step 1② is 0.5 mol / L to 3 mol / L; in step 1②, the pretreated sycamore fluff is immersed in the NaOH solution, stirred at room temperature for 1 to 2 hours, then allowed to stand and immersed for 8 to 10 hours, and then dried at 60°C to 80°C for 10 to 12 hours.

3. The preparation method of the Cu-BTC / Phoenix tung oil biomass carbon composite material according to claim 1, Features The carbonizing atmosphere described in step 1② is air, nitrogen or argon; in step 1②, the temperature is raised from room temperature to 300℃~450℃ at a heating rate of 5℃ / min~10℃ / min under the carbonizing atmosphere, and calcined at 300℃~450℃ for 30min~240min; in step 1③, the reaction product is washed with deionized water to neutrality, and then dried at 60℃~80℃ for 10h~12h to obtain a porous thin-layer tubular structure of tung oil cellulose porous carbon.

4. The method for preparing the Cu-BTC / Pu Tong fluff biomass carbon composite material according to claim 1, Features The copper salt described in step 2① is copper nitrate or copper sulfate; the mass ratio of the copper salt described in step 2① to deionized water is (2.5g~4.5g):30mL.

5. The method for preparing the Cu-BTC / Pu Tong fluff biomass carbon composite material according to claim 1, Features The organic ligand described in step 2② is 1,4-phthalic acid, 1,3,5-benzenetricarboxylic acid or 1,2-dimethylimidazole; the molecular weight of the polyvinyl pyrrolidone described in step 2② is 58000, 24000 or 1300000; the volume ratio of N,N-dimethylformamide and anhydrous ethanol in the mixed solution of N,N-dimethylformamide and anhydrous ethanol described in step 2② is (20-50):(20-50).

6. The method for preparing the Cu-BTC / Phoenix tung oil biomass carbon composite material according to claim 1, Features The mass volume ratio of the mixed solution of the organic ligand, polyvinyl pyrrolidone, N,N-dimethylformamide and anhydrous ethanol described in step 2② is (1g~2g):(1g~2g):60mL; the time of ultrasonic treatment described in step 2② is 5min~10min, the time of magnetic stirring is 15min~60min, and the speed of magnetic stirring is 500r / min~800r / min.

7. The method for preparing the Cu-BTC / Phoenix tung oil biomass carbon composite material according to claim 1, Features The volume ratio of solution I and solution II described in step 2③ is 1:2; the standing time described in step 2③ is 10h~12h; the washing described in step 2③ is washing 2 to 4 times with deionized water and anhydrous ethanol in sequence; the drying temperature described in step 2③ is 60℃~80℃, and the drying time is 5h~10h.

8. Application of a Cu-BTC / Phoenix tung oil biomass carbon composite material prepared by the preparation method according to claim 1, Features A Cu-BTC / Phoenix tung oil biomass carbon composite material is used to prepare gas sensors.

9. Application of the Cu-BTC / Phoenix tung oil biomass carbon composite material according to claim 8, Features A Cu-BTC / Phoenix tung blossom biomass carbon composite material is used to prepare a gas sensor, which is specifically completed in the following steps: adding the Cu-BTC / Phoenix tung blossom biomass carbon composite material to anhydrous ethanol, ultrasonically dispersing, and obtaining a uniformly dispersed suspension; spin-coating the uniformly dispersed suspension on an Au interdigital electrode, and drying at room temperature to obtain a gas sensor; the mass ratio of the Cu-BTC / Phoenix tung blossom biomass carbon composite material to the volume of anhydrous ethanol is (0.01g-0.05g):(0.3mL-1.0mL); the volume ratio of the uniformly dispersed suspension to the surface area of ​​the Au interdigital electrode is (0.03mL-0.15mL):0.25cm 2 .

10. Application of a Cu-BTC / Phoenix tung oil biomass carbon composite material according to claim 8 or 9, Features The gas sensor is used to detect low concentrations of NO in the air at room temperature. 2 Gas, the detection limit is as low as 30ppb.

Citation Information

Patent Citations

  • Method for preparing porous carbon micron tube from catkin, poplar seed or phoenix tree seed as raw material

    CN102557026A

  • Hydrothermal carbon-based composite material and preparation and application thereof

    CN110548487A

  • Large-size blocky biological framework / MOFs derived composite carbon material and preparation method thereof

    CN113697792A

  • Preparation method and application of biomass carbon material with hollow structure

    CN113929096A

  • Preparation method of biochar composite metal organic framework adsorption material

    CN114177891A

Cited By

  • Co-coated C / FHP catalyst and preparation method and application thereof

    CN121669236A